Draft Genome Sequences of Marine Isolates of Thalassomonas viridans and Thalassomonas actiniarum - Olonade, Israel; van Zyl, Leonardo Joaquim; Trindade, Marla (Genome announcements (Washington, DC), 2015)
Thalassomonas viridans and Thalassomonas actiniarum are aerobic Gram-negative bacilli which belong to a genus that has not received much attention, even though, as demonstrated here by the sequencing of their genomes, they are quite different from their closest relatives in current databases. Their genomes are relatively large at 7.7 and 7.4 Mb, respectively. This brief report describes the first draft genomes for any Thalassomonas species.